Potensi Pseudomonas sp. untuk Mengendalikan Penyakit Hawar Daun Bakteri (Xanthomonas oryzae pv. Oryzae) Secara In Vitro - Andree Saylendra; Nurmayulis Nurmayulis; Pina Ahdiani (Universitas Bangka Belitung, 2017)
This research was aimed to determine the potential of Pseudomonas sp. in controlling bacterial leaf blight disease (Xanthomonas oryzae pv. oryzae) in vitro. This research was conducted at the Laboratory of Agroecology, Faculty of Agriculture, University of Sultan Ageng Tirtayasa on June to September 2014. This research implemented experimental one factor that arranged in Completely Randomized Design with five replications. The treatment consisted of 6 isolates of Pseudomonas sp. (Ps 6, Ps 29, Ps 39, Ps 40, Ps 45, dan Ps 46) which was screened from the rhizosphere of roots of paddy plants. The inhibition of Pseudomonas sp. bacteria isolates was tested and showed that the results were not significantly different neither it was between each isolate nor against control (without treatment bacteria). Ps 39 isolate tend to had higher clear zone compare to other isolates.